The Impact of Exchange Rate on Output Level: Bounds Testing Approach for Pakistan (The Pakistan Development Review, 2012)
The stabilisation of growth process has been the aspiration of the nations in modern era. Since the industrial revolution in the world, most of the developing nations have been in the paradigm of chronic current account situation, loss in output, high import bill, less integration of their export sector, and less competitiveness in trade with the world. The process to devalue their currency may be evaluated as optimism for the improvement of their national growth that not only overcome the soaring trade deficit but also may be helpful to compete in international market. In theoretical literature, there has been contradiction among the researchers based on its effects in determining the net output of the economy. Since the work of Cooper (1971) and Krugman and Taylor (1978), the ambiguity arises for the effects of currency depreciation on output and their pioneer work explain the demand side as well as supply side channels through which depreciation may appear as loss in net output. The devaluation induces higher prices of tradable products that appear as loss in real balance of the economy and ultimately result in less output and growth. Some studies [Krugman and Taylor (1978); Edwards (1986) and Lizondo and Montiel (1989)] also support to contractionay output hypothesis with the induction of income redistribution channel that just redistribute income from the wage earners towards profit earners having the excess savings. This process ultimately leads to less aggregate demand as well as output via meager consumption. On the supply side, depreciation of currency result in higher input cost and less output level [Krugman and Taylor (1978); Van Wijnbergen (1986)]. In addition, wage indexation mechanism is also important that reduces the net benefits on producer side and escorts to the contraction in output [Agenor and Montiel (1996)].